(untitled) (Global Journal of Human-Social Science, 2023)
This paper starts with the assumption that translation is neither a transference nor a replacement of one word or symbol in one language with a word or symbol in another It is a matter of choice selecting the most appropriate or equivalent form to the original This paper argues that translators subjectivity and creativity play a significant role in striking a balance between what is accurate and what is acceptable during the translation process Although translation is based on the source text its outcome depends essentially on the translator s own realization and perception of the text Therefore it may be difficult to approach translation from decoding and encoding perspectives because words and phrases change over the years However at the heart of the translation process there is the translator s free will which determines the outcome and quality of the text to be translated